PENERAPAN HUKUM PIDANA DALAM KEJAHATAN SKIMMING - Dyah Ayuworo Sukenti (Fakultas Hukum Universitas Janabadra, 2022)
Along with the times, there are more and more ways that skimming criminals do in committing crimes. Increased security that is always being improved cannot be a barrier. The law governing the crime of skimming is still very general, there is no strong explanation that describes the process of skimming events occurring. There are no articles that regulate the number of crimes caused by skimming. As with the laws in the states of the United States, which have clearly regulated both the process of skimming crimes and crimes in the development of skimming crimes, for example buying and selling data obtained from skimming to buying and selling duplicate debit or credit cards that can withdraw the victim's money from the personal data obtained. The need for change is very far behind in the regulation of technological crimes.